Mesoporous SiO2 nanostructure: Light-induced adsorption enhancement and its application in photocatalytic degradation of organic dye. Issue 18 (15th December 2019) - Wu, Yetong; Du, Xuanzhen; Kou, Yumeng; Wang, Youqing; Teng, Feng
Abstract: Mesoporous SiO2 nanostructure was synthesized by a simple controlled hydrolysis process. The obtained mesoporous SiO2 nanostructure was composed of amorphous silica nanoparticles and exhibits significant light-induced adsorption performance. The light-induced adsorption enhancement may be caused by exchanging adsorption between hydroxyl groups and dye molecules because the adsorption process under light irradiation exhibits significant chemical adsorption property. Combining this mesoporous SiO2 and rutile TiO2 materials, the obtained hybrid photocatalyst displays superior photocatalytic degradation performance of RhB dye due to the excellent adsorption performance and the increase of surface defects on the surface of TiO2 nanostructure. These results provide novelty route for the further design and development of high performance photocatalyst in actual application.